FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA ADIDAS DI GROBOGAN - Anwar, Zaenul; Octavia, Ayu Nurafni (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
There are fluctuations in the top brand index which tends to decrease in the last 4 years for Adidas sports shoes. This research aims to examine the influence of brand image, price perception and product quality on purchasing decisions for Adidas sports shoes in Grobogan Regency. The sample used was 96 with a purposive sampling technique from the Grobogan community, consumers of Adias sports shoes. Data collection used a Google Form questionnaire and the results of quantitative analysis included validity, reliability, classical assumption tests, multiple regression analysis, hypothesis testing via t test, testing. model with the f test, as well as the coefficient of determination (R2). The tool used to process the data is SPSS version 23. The results of this research show that brand image has a positive and significant influence on purchasing decisions, price perception also has a positive and significant influence on purchasing decisions, while product quality has no influence on purchasing decisions. Simultaneously brand image, price perception and product quality have an influence on purchasing decisions by 93.6% of the coefficient of determination test and the remainder is influenced by factors not examined in this research